The The Relationship of Service Quality with Visitor Satisfactions At The Permanent Exhibition of The Indonesian National Gallery Collection - Dinda Izzah Khalida (The Islamic Education and Multiculturalism Foundation, 2022)
This study discusses service quality in terms of the five dimensions of service quality tangible, reliability, responsiveness, assurance, and empathy at the permanent exhibition of the Indonesian National Gallery collection with visitor satisfaction during the Covid-19 pandemic. The method used in this study is a quantitative method with descriptive statistical analysis and correlation analysis. This study aims to determine the relationship between service quality in terms of tangibles, reliability,responsiveness,assuranceandempathywithvisitor satisfaction at the National Gallery of Indonesia. Respondents in this study amounted to 98 people with data collection techniques that is accidental sampling conducted at the National Gallery of Indonesia. The results of this study indicate that there is a significant relationship between service quality in terms oftangibles, reliability, responsiveness, assurance, and empathy with visitor satisfaction at the National Gallery of Indonesia. The results of this study indicate that there is a relationship between service quality in terms of tangible dimensions. Reliability, responsiveness and empathy with visitor satisfaction during the covid-18 pandemic. The tangible, assurance, and empathy relationships have a moderate and significant relationship with visitor satisfaction during the COVID-19 pandemic, while the reliability and responsiveness dimensions have a low but definite relationship with visitor satisfaction during the pandemic